2011
DOI: 10.1016/j.theriogenology.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Administration of human chorionic gonadotropin at embryo transfer induced ovulation of a first wave dominant follicle, and increased progesterone and transfer pregnancy rates

Abstract: Theriogenology 75 (2011) 1506-1515. doi:10.1016/j.theriogenology.2010.12.012Received by publisher: 2010-08-02Harvest Date: 2016-01-04 12:21:09DOI: 10.1016/j.theriogenology.2010.12.012Page Range: 1506-151

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…In the current study, response rates using Ovsynch were well below expected outcomes (63.3 vs. 87%). Success rates in previous reports using hCG to cause a spontaneous ovulation and induce an acces-sory CL were approximately 70% (Wallace et al, 2011;Stevenson and Pulley, 2012). The observed response in the current study to hCG to induce an accessory CL (36%) was also less than expected.…”
Section: Discussioncontrasting
confidence: 68%
“…In the current study, response rates using Ovsynch were well below expected outcomes (63.3 vs. 87%). Success rates in previous reports using hCG to cause a spontaneous ovulation and induce an acces-sory CL were approximately 70% (Wallace et al, 2011;Stevenson and Pulley, 2012). The observed response in the current study to hCG to induce an accessory CL (36%) was also less than expected.…”
Section: Discussioncontrasting
confidence: 68%
“…Wallace et al [13] demonstrated improved pregnancy rates after an intramuscular injection of hCG at ET in cows. In a study by Banerjee and Fazleabas [14], intrauterine injection of hCG in baboons induced a favorable uterine environment for embryo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of hCG at embryo transfer (ET) has resulted in an increased pregnancy rate in animal models [13]. Intrauterine injection of hCG has been associated with significant pro-implantation changes of the endometrium in primates [14].…”
Section: Introductionmentioning
confidence: 99%
“…Small et al (2004) were also unable to improve pregnancy rates in Bos taurus recipients treated with GnRH or pLH on Days 5 or 7 after oestrus. In a very recent study (Wallace et al 2011), 719 beef recipients alternately received 1000 IU hCG or saline (control) at the time of embryo transfer. Serum progesterone concentrations at pregnancy diagnoses in pregnant cows were higher after hCG treatment than in controls, and conception rates were 61.8 and 53.9% for hCG and control groups, respectively.…”
Section: Other Treatments Designed To Increase Pregnancy Rates In Recmentioning
confidence: 99%